2021
DOI: 10.1515/cclm-2021-0278
|View full text |Cite
|
Sign up to set email alerts
|

S100B protein, cerebral ultrasound and magnetic resonance imaging patterns in brain injured preterm infants

Abstract: Objectives The early detection of preterm infants (PI) at risk for intraventricular hemorrhage (IVH) and neurological sequelae still constitutes an unsolved issue. We aimed at validating the role of S100B protein in the early diagnosis and prognosis of IVH in PI by means of cerebral ultrasound (CUS) and magnetic resonance imaging (MRI) today considered standard of care procedures. Methods We conducted an observational case-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…In the perinatal period, there is growing evidence that the pathophysiological cascade of events involved in CNS development and damage are still not fully elucidated and are subjects of investigation. More recently, it has been shown that among a series of NB, S100B appears the only one fulfilling the majority of the criteria requested by FDA, EMA and NIH statements [ 10 , 19 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the perinatal period, there is growing evidence that the pathophysiological cascade of events involved in CNS development and damage are still not fully elucidated and are subjects of investigation. More recently, it has been shown that among a series of NB, S100B appears the only one fulfilling the majority of the criteria requested by FDA, EMA and NIH statements [ 10 , 19 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The finding deserves further consideration bearing in mind that at this time period the brain volume, weight and structure are at their highest growing level [ 28 31 ]. In particular: i) magnetic resonance imaging (MRI) patterns were suggestive of the timing and duration of different myelinisation processes at the stage under investigation [ 30 ], ii) the assessment in biological fluids of NB such as S100B, activin A, G-FAP were in agreement with MRI patterns and with the biochemical, morphological and electrophysiological maturation of the CNS [ 2 4 , 19 , 28 , 31 ], and iii) near infrared spectroscopy patterns in the late preterm period, in healthy infants, showed an improved oxygenation status and increased tissue function suggestive of CNS development [ 32 34 ]. On the basis of the present findings, it is reasonable to support a LT CNS trophic role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among several NB currently under investigation (glial fibrillary acid protein, GFAP; activin A, adrenomedullin, oxidative stress, neuron specific enolase), the S100B protein, mainly located in glial cells and in neuronal subpopulations of the central nervous system (CNS), has been suggested as a trustable marker in different biological fluids [1][2][3][4][5][6][7][8][9][10]. It's easy measurability, reproducibility, and assessment in invasive (cerebrospinal, CSF; blood) and non-invasive biological fluids (urine, saliva) support its usefulness as an early marker of brain development/injury in neonatal intensive care units (NICU) daily practice [10][11][12]. Before this can be done, a few issues still need to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Today, magnetic resonance imaging (MRI) is considered the gold standard for perinatal brain damage detection and prognosis in newborns complicated by intraventricular hemorrhage (IVH), perinatal asphyxia (PA) and hypoxic ischemic encephalopathy (HIE) [13,14]. In this regard, it has been previously reported that MRI patterns correlated with long-term neurodevelopment in preterm and term infants [10,11]. In the latter, the basal ganglia/watershed (BG/W) score was able to identify infants at risk for poor neuromotor and cognitive outcome at 3-12 months of age, respectively [10].…”
Section: Introductionmentioning
confidence: 99%